2018
DOI: 10.1111/jvh.12928
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: Development of hepatocellular carcinoma in chronic hepatitis B patients with hepatitis e antigen seroconversion

Abstract: Hepatitis B e antigen (HBeAg) seroconversion is considered to have significantly favourable clinical outcomes for patients with chronic hepatitis B (CHB). However, inconsistent study results suggest that hepatocellular carcinoma (HCC) still occurs in patients with HBeAg seroconversion. We performed a systematic review and meta-analysis to determine the incidence of HCC in patients with CHB after HBeAg seroconversion. Web of Science, PubMed and Embase databases were searched through January 2017. The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
(186 reference statements)
0
23
0
Order By: Relevance
“…Few reports are related to tissue samples because of the difficulty in sample collection. Since the development of HCC is closely related to CIR and hepatitis [112,113,114], there are also many literatures that compare these liver diseases together. It is hoped to uncover the relationship between hepatitis, CIR and HCC, and it is also hoped to discover some specific markers that can distinguish these diseases.…”
Section: Alteration Of Acylcarnitine Metabolism In Hccmentioning
confidence: 99%
“…Few reports are related to tissue samples because of the difficulty in sample collection. Since the development of HCC is closely related to CIR and hepatitis [112,113,114], there are also many literatures that compare these liver diseases together. It is hoped to uncover the relationship between hepatitis, CIR and HCC, and it is also hoped to discover some specific markers that can distinguish these diseases.…”
Section: Alteration Of Acylcarnitine Metabolism In Hccmentioning
confidence: 99%
“…Even when the patients were censored at the time of AVT discontinuation, the overall results were not changed (data not shown). However, in actual clinical practice, clinicians frequently provide life‐long AVT in patients with CHB infection who achieved ESC, owing to concerns of progression to cirrhosis or HCC development in addition to HBV relapse 41 . Indeed, in our study, only 12.7% of the training cohort and 8.6% of the validation cohort discontinued AVT.…”
Section: Discussionmentioning
confidence: 77%
“…To our knowledge, no well‐conducted, controlled study of whether AVT discontinuation increases the risk of HCC development after ESC has been published. Also, a recent meta‐analysis showed that AVT discontinuation is not a risk factor for HCC development after HBeAg seroconversion 41 . However, it has been shown that long‐term AVT can reduce the risk of HCC development in patients with CHB 7‐9 .…”
Section: Discussionmentioning
confidence: 99%
“…The average age of HBeAg‐positive patients in our sample was 45 years, which indicates worse outcomes as later seroconversion is linked to complications like liver cirrhosis 7 . Patients with cirrhosis, active hepatitis, or older than 40 years of age at the time of HBeAg seroconversion are also at significantly higher risk for HCC development 13 …”
Section: Discussionmentioning
confidence: 99%
“…7 Patients with cirrhosis, active hepatitis, or older than 40 years of age at the time of HBeAg seroconversion are also at significantly higher risk for HCC development. 13 Moreover, less than one-fifth of hepatitis B patients with positive HBeAg, and only one-third of patients with negative HBeAg in Bahrain are on antiviral therapy. We did not collect data on time of diagnosis, previous treatment, or length of current treatment, and we cannot comment on the significance of this.…”
Section: Discussionmentioning
confidence: 99%